Ulnar Nerve Compression in the Proximal Forearm By An Intraneural Arteriovenous Malformation. (September 2015) - Saquib, Mohd; Khan, Nida; Mir, Altaf
Compression of the ulnar nerve is most commonly caused by ganglions, lipomas, anomalous tendon and muscles, trauma related to an occupation and arthritis in the upper limb; however, nerve compression in the upper limb and, more importantly, in the proximal forearm by a vascular lesion is rare. A rare case of ulnar nerve compression in the proximal forearm by an arteriovenous malformation in a 45-year-old man who presented with six-year history of gradually increasing swelling in medial aspect of proximal forearm is reported. After excision of the tumour, it was found to be an arteriovenous malformation.